Implementación de prácticas higiénicas para el mejoramiento de la calidad microbiológica de la leche saborizada en la planta procesadora de soya instalada en las malvinas en el suburbio de Guayaquil - Benítez Silva, Lorena Alexandra (2009)
In the Cooperative 24 May (Malvinas), located in the southern suburb of Guayaquil, working a production of soy milk called "Mechanical Cow" which was designed, installed and put into operation by a team of students of Industrial Engineering , Mechanical and Food of the FIMCP ESPOL. The plant began operation in September 2008 until March 2009 have worked with good hygienic practices not in contravention of food safety. After a diagnosis of GMP compliance through Checklists from receipt of raw materials to the office, microbiological analysis stages and possible causes of contamination identified in the Cause-Effect Diagram performed as well Verificatorio a diagnosis of the cleaning of surfaces in contact with food for the luminometer, microbial contamination was found with E. Coli Heavy stages, blending and packaging, and excessive aerobic mesophilic count in the mixing, filtering and packaging. The objective of this project therefore focused on the implementation of procedures and improvements to ensure the production of soy milk safe, with reference to the standards set by BPM. Using as basis the standards of Ecuador B. PM, Codex Alimentarius CAC / RCP 1 - 1969 and American law 21 - CFR 110, there were improvements, which were ranked for further implementation and staff training. Some improvements could not be implemented, mainly due to resource constraints and are being controlled with the recommendation that its implementation should hacérsela as soon as possible to prevent future contamination of the product. Finally, soy milk meets the microbiological criteria INEN Standard 10: 2003 Third REVIEW pasteurized cows milk in total coliforms, and specifications of Guatemalan legislation COGUANOR NTG-3403 for pasteurized soy milk, as evidenced by the absence of total coliforms, E. Coli, molds and yeasts and the value of 260 CFU / ml in aerobic plate counts, a result that was validated with the test conducted by the Laboratory prothallus-ESPOL (1.5 x 10 CFU / ml of aerobic plate counts and absence of total coliforms), ensuring that the production process is being carried under hygienic practices. Must be stressed that these achievements are due also to changes in behavior and personal hygiene product of the training conducted and monitoring the implementation of the procedures developed.